3D printed highly elastic strain sensors of multiwalled carbon nanotube/thermoplastic polyurethane nanocomposites. (5th October 2017) - Christ, Josef F.; Aliheidari, Nahal; Ameli, Amir; Pötschke, Petra
Abstract: 3D-printable, flexible, and conductive thermoplastic-based material was successfully developed for strain sensing applications. Thermoplastic polyurethane/multiwalled carbon nanotube (TPU/MWCNT) were compounded, their filaments were extruded, and the sensors 3D printed using fused deposition modeling. Mechanical, electrical, and piezoresistivity behaviors were investigated under monotonous and cyclic loadings. MWNCTs enhanced the printing capability of TPU by increasing its stiffness. Very modest decreases were observed in the elasticity modulus of printed nanocomposites ( 14%, compared to that of bulk counterparts), indicating excellent interlayer adhesion and superior performance to those reported in literature. Consequently, the conductivity was largely preserved after printing, in both through-layer and cross-layer directions. The piezoresistivity gauge factors of as high as 176 were achieved under applied strains as large as 100%. A highly repeatable resistance-strain response was also obtained under cyclic loadings. The results demonstrate TPU/MWCNT as an excellent piezoresistive feedstock for 3D printing with potential applications in wearable electronics, soft robotics, and prosthetics, where complex design, multi-directionality, and customizability are demanded. Graphical abstract: Highlights: Flexible TPU/MWCNT was successfully 3D-printed as a sensing sensor. The presence of MWCNT enhanced the printability of TPU. Mechanical and electrical properties were highly preserved after 3D printing. Printed sensors showed excellent cyclic piezoresistivity behavior. Gauge factors as high as 176 were achieved.